2008
DOI: 10.1038/jes.2008.32
|View full text |Cite
|
Sign up to set email alerts
|

Levels of urinary total and speciated arsenic in the US population: National Health and Nutrition Examination Survey 2003–2004

Abstract: Objective: To provide levels of total and speciated urinary arsenic in a representative sample of the US population. Methods: For the first time, total arsenic and seven inorganic and organic arsenic species were measured in the urine of participants (n ¼ 2557) for the [2003][2004] National Health and Nutrition Examination Survey (NHANES). Data were compiled as geometric means and selected percentiles of urinary arsenic concentrations (mg/l) and creatinine-corrected urinary arsenic (mg/g creatinine) for total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
110
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(124 citation statements)
references
References 27 publications
12
110
0
2
Order By: Relevance
“…This population does not show, based on the FIQ, high consumption of fish (8%) or shellfish (6%). The geometric means for DMA and AsB (3.8 and 4.4 mg/l, respectively) in our study are very similar to what has been found in the 2000-2003 NHANES (3.8 and 1.8 mg/l, respectively) (Caldwell et al, 2009) and in individuals who did not eat seafood in the 2003-2006 NHANES (3.5 and 1.3 mg/l, respectively) (Navas-Acien et al, 2011). Several studies have also reported elevated concentrations of urinary AsB in populations that consumed little or no fish or seafood (Lai et al, 2004;Brima et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…This population does not show, based on the FIQ, high consumption of fish (8%) or shellfish (6%). The geometric means for DMA and AsB (3.8 and 4.4 mg/l, respectively) in our study are very similar to what has been found in the 2000-2003 NHANES (3.8 and 1.8 mg/l, respectively) (Caldwell et al, 2009) and in individuals who did not eat seafood in the 2003-2006 NHANES (3.5 and 1.3 mg/l, respectively) (Navas-Acien et al, 2011). Several studies have also reported elevated concentrations of urinary AsB in populations that consumed little or no fish or seafood (Lai et al, 2004;Brima et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, there was no significant difference between the mean UAs concentrations between the three groups, but the levels were higher than the US population data indicating possible exposure. Both seafood and rice can contribute to elevated UAs levels [27][28][29][30]. In the present study, we did not gather information about the sea fish intake of the participants.…”
Section: Discussionmentioning
confidence: 86%
“…In a recent analyses of NHANES (National Health and Nutrition Examination Survey) data, average urinary total arsenic concentrations were 8.30 µg/L (95% CI, 7.19-9.57) (Caldwell et al 2008). Using data from the same nationally representative cross-sectional survey of the U.S. population, Navas-Acien and colleagues (2008) found that participants with type 2 diabetes had a 26% higher level of total arsenic (95% CI, 2.0-56.0) and the OR for type 2 diabetes comparing participants at the 80th versus the 20th percentiles was 3.58 for the level of urinary total arsenic (95% CI, 1.18-10.83).…”
Section: Discussionmentioning
confidence: 99%